Short-term risk and long-term incidence rate of infection and malignancy with IL-17 and IL-23 inhibitors in adult patients with psoriasis and psoriatic arthritis: a systematic review and meta-analysis - Wu, Shuwei; Xu, Yuanyuan; Yang, Lihua; Guo, Linghong; Jiang, Xian (Frontiers in Immunology, 2023)
The risk of infection and malignancy may be a concern for patients with psoriasis receiving interleukin (IL)-17 and IL-23 inhibitors, particularly with long-term treatments. We aimed to estimate the short-term risks and long-term incidence rates of infection and malignancy with IL-17 or IL-23 antagonists in adult patients with psoriasis and psoriatic arthritis through this comprehensive meta-analysis (PROSPERO registration number: CRD42022363127). We searched PubMed, MEDLINE, Web of Science and ClinicalTrials.gov until May 17, 2023 for randomized placebo-controlled trials and long-term (≥ 52 weeks) open-label extension studies. The estimates of short-term risk ratios (RRs) and long-term exposure-adjusted incidence rates (EAIRs) were pooled using R software 4.1.1 and STATA 16.0. This review included 45 randomized placebo-controlled studies and 27 open-label extension studies. Short-term RRs of serious infection, overall infection and malignancy were 1.45 (95% confidence intervals, 95% CI: 0.81-2.59), 1.20 (95% CI: 1.06-1.35), 0.83 (95% CI: 0.41-1.71) with IL-17 inhibitors; and 0.68 (95% CI: 0.38-1.22), 1.13 (95% CI: 1.00-1.28), 0.87 (95% CI: 0.37-2.04) with IL-23 inhibitors. Increased short-term risks of nasopharyngitis and Candida infection with IL-17 inhibitors were found. Long-term EAIRs of serious infection, overall infection, nonmelanoma skin cancer (NMSC), malignancies excluding NMSC, nasopharyngitis and upper respiratory tract infection were 1.11/100 patient-years (PYs), 57.78/100PYs, 0.47/100PYs, 0.24/100PYs, 15.07/100PYs, 8.52/100PYs, 3.41/100PYs with IL-17 inhibitors; and 1.09/100PYs, 48.50/100PYs, 0.40/100PYs, 0.43/100PYs, 10.75/100PYs, 5.84/100PYs with IL-23 inhibitors. Long-term EAIR of Candida infection was 3.41/100PYs with IL-17 inhibitors. No active or reactivated tuberculosis was ever reported in all the trials, and only a few cases of latent tuberculosis, hepatitis, and herpes zoster were reported during the long-term extension periods. No evidence of increased EAIRs of infection and malignancy with longer durations was found. Our study suggested that short-term risk and long-term incidence of infections and malignancies in psoriasis patients receiving IL-17 inhibitors and IL-23 inhibitors are generally low. However, close monitoring is required for nasopharyngitis and Candida infection with IL-17 inhibitors. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42022363127.